2021
DOI: 10.4049/jimmunol.2100254
|View full text |Cite
|
Sign up to set email alerts
|

Liver-Dependent Lung Remodeling during Systemic Inflammation Shapes Responses to Secondary Infection

Abstract: The gene expression data presented in this article have been submitted to the National Center for Biotechnology Information's Gene Expression Omnibus (https://www.ncbi.nlm. nih.gov/geo/) database under accession number GSE167277. The mass spectrometry proteomics data have been submitted to the ProteomeXchange Consortium (http:// proteomecentral.proteomexchange.org/cgi/GetDataset) via the PRIDE partner repository under accession number PXD024663.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 86 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…Lungs were prepared for histology and immunofluorescence as previously described ( 57 , 58 ). Frozen sections (8 μM) were fixed, permeabilized with 0.2% Triton-X, and blocked with 10% donkey serum and 3% bovine serum albumin (blocking buffer).…”
Section: Methodsmentioning
confidence: 99%
“…Lungs were prepared for histology and immunofluorescence as previously described ( 57 , 58 ). Frozen sections (8 μM) were fixed, permeabilized with 0.2% Triton-X, and blocked with 10% donkey serum and 3% bovine serum albumin (blocking buffer).…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, the fluorescence was observed in the livers and spleens, whereas the signals in the hearts and kidneys were minimal ( Figure S3 A). Previous studies in mice demonstrated that pneumonia in the lung induces inflammatory response in liver ( Odom et al., 2021 ; Quinton et al., 2012 ). In addition, acute P. aeruginosa lung infections result in bacterial dissemination in blood and liver ( Pène et al., 2012 ; Gonçalves-de-Albuquerque et al., 2016 ; Ren et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%